Eksplorasi media Balok Dienes dalam mengakomodasi keberagaman siswa pada pembelajaran Matematika di sekolah dasar - Hafifah, Shintia; Trisniawati, Trisniawati; Rahim, Abdul (Literal: Disability Studies Journal, 2023)
This study aims to describe the use of Dienes beam media for third grade students who have problems in learning mathematics, namely students are less active and less enthusiastic in participating in the learning process. The results of this study are (1) Planning for learning mathematics using The Dienes block media (2) The process of using The Dienes block media in learning mathematics with the concept of addition and subtraction for class III students of SD Negeri Glagah. This research was conducted at SD Negeri Glagah Yogyakarta starting on January 20 2023 until February 28 2023. The method used in this research is a qualitative descriptive method. The primary data were in the form of interviews and observations obtained from the results of interviews with teachers and third grade students, while the secondary data in this study were the results of student research documentation. Researchers in analyzing data used an interactive model from Miles and Huberman which was divided into several stages, namely data collection, data reduction, data display, and conclusion drawing/verification. Checking the validity of the researcher's data uses triangulation and increases persistence.